Humpty Dumpty's Kaleidoscope : A new generation of German artists. - Murphy, Bernice (Sydney : Museum of Contemporary Art, 1992)
Bosslet, Eberhard ; Brandmeier, Monika, Denda, Elke ; Eichhorn, Maria ; Ginkel, Andreas ; Görlich, Ulrich ; Grünfeld, Thomas ; Gütnher, Ingo ; Heisterkamp, Fritz ; Hildebrand, Christoph ; Höfer, Candida ; Hoffmann, Nina ; Kaeseberg ; Kneffel, Karin ; Loch, Anne ; Locher, Thomas ; Mayer, Maix ; Nestler, Stefan ; Nicolai, Olaf ; Pallanca, Heike ; Pitz, Hermann ; Prinz, Bernhard ; Robbe, Wolfgang ; Thiel, Frank
Humpty Dumpty's Kaleidoscope : A new generation of German artists, Museum of Contemporary Art, Sydney, 9 Oktober 1992 - 28 February 1993
English
kunstcatalogus
Keywords: Duitsland